Time-on-task decrement in vigilance is modulated by inter-individual vulnerability to homeostatic sleep pressure manipulation - Maire, Micheline; Reichert, Carolin F.; Gabel, Virginie; Viola, Antoine U.; Krebs, Julia; Strobel, Werner; Landolt, Hans-Peter; Bachmann, Valérie; Cajochen, Christian; Schmidt, Christina (Frontiers in Behavioral Neuroscience, 2014)
Under sleep loss, vigilance is reduced and attentional failures emerge progressively. It becomes difficult to maintain stable performance over time, leading to growing performance variability (i.e. state instability) in an individual and among subjects. Task duration plays a major role in the maintenance of stable vigilance levels, such that the longer the task, the more likely state instability will be observed. Vulnerability to sleep-loss-dependent performance decrements is highly individual and is also modulated by a polymorphism in the human clock gene PERIOD3 (PER3). By combining two different protocols, we manipulated sleep-wake history by once extending wakefulness for 40 h (high sleep pressure condition) and once by imposing a short sleep-wake cycle by alternating 160 min of wakefulness and 80 min naps (low sleep pressure condition) in a within-subject design. We observed that homozygous carriers of the long repeat allele of PER3 (PER35/5) experienced a greater time-on-task dependent performance decrement (i.e., a steeper increase in the number of lapses) in the Psychomotor Vigilance Task compared to the carriers of the short repeat allele (PER34/4). These genotype-dependent effects disappeared under low sleep pressure conditions, and neither motivation, nor perceived effort accounted for these differences. Our data thus suggest that greater sleep-loss related attentional vulnerability based on the PER3 polymorphism is mirrored by a greater state instability under extended wakefulness in the short compared to the long allele carriers. Our results undermine the importance of time-on-task related aspects when investigating inter-individual differences in sleep loss-induced behavioural vulnerability.